The ADELE Corpus of Dyadic Social Text Conversations:Dialog Act Annotation with ISO 24617-2 - Campbell, Nick; Wade, Vincent; Spillane, Brendan; Gilmartin, Emer; O'Reilly, Maria; Saam, Christian; Su, Ketong; Clark Leigh; Cowan, Benjamin R.; Levacher, Killian; Calvo, Arturo; Cerrato, Loredana (European Language Resources Association (ELRA), 2018)
Social or interactional dialog is less well described than task-based or instrumental dialog, although there is increasing interest in the genre, particularly in light of new spoken and text dialog applications which aim to relate to the user as well as perform tasks. Dialog act annotation aids understanding of interaction structure; essential to the design of successful artificial dialog. Much social text interaction may be closer to social talk than to traditional written language. In this paper we briefly describe social or casual talk, and review how current dialog annotation schemes and particularly the ISO standard 24617-2 (Semantic annotation framework, Part 2: Dialogue Acts)treat non-task elements of dialog. To aid in training a casual talk system, we collected a corpus of 193 dyadic text dialogs, based on a novel ‘getting to know you’ social dialog elicitation paradigm. We describe the annotation of the dialogs, and propose additional acts to better cover greeting and leave taking. We report on preliminary analyses of the corpus, and provide an overview of the corpus content and its relationship to spoken language. The corpus, coding manual, and annotations are being packaged and will be made available to interested researchers.
LREC
Keywords: Casual conversation; Dialog corpus; Dialog acts; Digital Engagement; Casual Conversation; Dialog Acts; Dialog Corpus; Communication